Find What You Need, Understand What You Find - Marchionini, G.; White, R.W.; White, Ryen W. (International Journal of Human-Computer Interaction, 2007)
The developments of the fields of Human-Computer Interaction (HCI) and Information Retrieval (IR) have followed parallel streams with both achieving significant impact in the early part of the 21st century. The intersection of these two areas engages an active community of researchers who have influenced user interfaces for World Wide Web (WWW) sites and search engines (Marchionini, 2006). The roots of this confluence of research were nourished by pioneers in several areas, including hypertext and later in digital libraries. Of particular importance is the work of Ben Shneiderman and his collaborators at the University of Maryland‘s Human Computer Interaction Laboratory (HCIL). Shneiderman not only served as an inspirational leader for others aiming to understand how people search for and use digital resources, but he also is a hands-on pioneer in developing novel user interfaces that support the information seeking process. Although his work has significant impact in other HCI areas as well, the focus on this paper is the current state of effective and usable systems for information seeking.